Conduta Terapêutica na Coagulação Intravascular Disseminada e na Fibrinólise - Famadas, Luiz Carlos (2023)
The author comments on diagnostic difficulties of disseminated intravascular coagulation (DIC and fibrinolisis (F) and suggests a compact laboratory work up necessary to diagnosis in both disturbances. Enphasis is placed on the therapeutic approach of patients with DIC and F, stressing the following points: 1) Removal of etiological factors and restoration of blood volume are the two main concerns. 2) infusions of coagulation factors and platelets are not important; the infusion of fibrinogen concentrate is contraindicated. 3) Heparin and antifibrinolitics are usually administered to patients with chronic DIC and F prior to surgical procedures to eliminate causative pathology. 4) Fibrin and fibrinogen degradation Products do persist in circulation above hemostatic levels for a few hours after the causative pathology has been removed. Bleeding during this period does not demand specific treatment except for maintenance of blood volume.